Nanoemulsion through cold emulsification: An advanced cold manufacturing process for a stable and advanced drug delivery system - Pankaj Bhatt, Tanvi Bhatt, Vikas Jain, Rupshee Jain, Papiya Bigoniya (Journal of Applied Pharmaceutical Science, 2024)
The personal care and pharmaceutical industries use emulsion science and its by-products extensively to create creams and lotions that include both water and oil-soluble ingredients. Although it is predicted that cooling and heating alone account for over 90% of the overall expenditure of energy used for the manufacture of an emulsion system, present methods for processing such emulsions demand large amounts of time and energy. The cold process of emulsion technologies will become more preferable to consumers and consumer has started showing interest in sustainable and environment-friendly products and procedures. An advanced cold emulsification method of manufacturing a topical semisolid dosage form has been developed for an advanced drug delivery system in the form of nanoemulsion to overcome the manufacturing challenges of thermolabile drugs and to have a sustainable and eco-friendly cost-effective drug delivery when compared to conventional topical dosage forms. The creation of nanoemulsions will result in a formulation that is thermodynamically stable and combines two immiscible liquids to create a stable homogenous combination in the presence of an appropriate stabilizer. The stability and droplet size of a nanoemulsion makes it different from a regular emulsion; the smaller droplet size increases its stability and penetration through the skin’s epidermis. In this review, the emphasis is on providing a basic understanding of cold emulsification as a formulation technique for nanoemulsions, its characterization, applications, and various patents and clinical trials involving nanoemulsions. This information can serve as the foundation for further developing and improving current techniques and technology involving nanoemulsions.
Keywords: Cold emulsification, nanoemulsion, high-pressure homogenization, thermolabile drugs, industrial application